Psycholinguistic Insights into Lexical Choice and Emotion: The Case of Bill Gates’ 2007 Harvard Commencement Speech - Mukti, Muhammad Abdee Praja; Listiani, Toneng; Wardoyo, Cipto (Program Studi Pendidikan Bahasa Inggris, 2025)
This study explores the psycholinguistic dimensions of lexical choice and emotional expression in Bill Gates’ 2007 Harvard Commencement Speech. Drawing on a qualitative descriptive methodology and discourse analysis of the speech transcript, this research investigates how Gates strategically employs emotionally charged vocabulary, humor, metaphors, and narrative structures to evoke specific emotional responses, foster audience engagement, and advocate for social change. The findings reveal that Gates utilizes high-emotion lexical items such as regret, inequity, and disparity to highlight global injustices while employing self-deprecating humor to reduce psychological distance and build rapport with the audience. Metaphorical constructs further enhance cognitive processing and emotional resonance by simplifying complex societal issues. This paper extends its analysis to emphasize the educational implications of Gates’ linguistic strategies, particularly in relation to public speaking pedagogy, emotional intelligence in communication, and the role of language in shaping critical thinking and social awareness. The study contributes to the understanding of psycholinguistic dynamics in influential public discourse and underscores the importance of integrating affective and cognitive dimensions in language education.